The Aston Forensic Linguistic Databank (FoLD) - Petyko, Marton; et al. (Language and Law / Linguagem e Direito, 2022)
The Aston Forensic Linguistic Databank (FoLD) is a permanent, controlled access online repository for forensic linguistic data. We broadly understand forensic linguistics as any academic research with a potential to improve the delivery of justice through the analysis of language. FoLD thus comprises a wide range of datasets with relevance to forensic linguistics and language and law, including commercial extortion letters, investigative interviews in police and other contexts, legal documents, forum posts from far-right online groups, and comment threads from political blogs. This paper outlines how FoLD works and its potential impact on the general discipline of forensic linguistics.